Ethics of future accounting professionals: Evidence from Malaysia - Abu Bakar, Nur Barizah; Ismail, Suhaiza; Mamat, Suaniza (Emerald Group Publishing Limited, 2008)
A strong ethical sense needs to be imbued in potential entrants to the accountancy profession. This paper explores the ethical attitudes of the final year accounting students in the International Islamic University Malaysia. There were 210 students who responded to the self-administered questionnaire survey. Of these respondents, 38 per cent would opt to become whistleblowers. About 3 per cent would accept bribes. Once an element of risk of being caught was introduced, the percentage opting for whistleblowing increased by 6 per cent. however, none chose the bribe option. These responses indicate that only a small proportion of students will depend on punishment and penalty in order to behave ethically. A larger proportion of male students as compared to female tend to behave unethically. The study indicates that the majority of respondents would prefer not to indulge in unethical behavior. The primary contribution of this paper isthat it offers insight on Malaysian accountancy students' ethical attitudes.